Analisis Asphalt Concrete Wearing Course (AC-WC) dengan Penambahan Lateks dan Abu Sekam Padi pada Perkerasan Jalan - Prabowo Pujito; Zida Shofwan Azhim; Eko Muliawan Satrio (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Asphalt Concrete Wearing Course (AC-WC) is a wearing layer on flexible pavements that directly receives traffic loads and environmental influences. However, conventional mixtures are still susceptible to plastic deformation, fatigue cracking, and water damage, so material modification is needed to improve their performance. This study aims to analyze the effect of adding latex and rice husk ash on the Marshall characteristics of AC-WC and to determine the optimal mixture variation. Laboratory experimental methods were used with 60/70 penetration asphalt, aggregates in accordance with the 2025 General Specifications for Highways, latex as an additive, and rice husk ash as a filler, with variations of 0%, 4%, 7%, and 9% latex and 0%, 3%, 6%, and 7% rice husk ash. Marshall test results showed that the combination of materials significantly affected the stability, flow, and stiffness of the mixture, while still meeting Bina Marga technical requirements. The best mixture was obtained with 3% latex and 6% rice husk ash, with VIM 4.82%, VMA 21.63%, VFB 78.01%, stability 831.17 kg, flow 3.73 mm, and MQ 222.33 kg/mm, making this variation recommended as the optimal and environmentally friendly AC-WC mixture.